2022
DOI: 10.36418/cerdika.v2i4.371
|View full text |Cite
|
Sign up to set email alerts
|

Tinjauan Kelengkapan Pengisian Formulir Assesment Awal Poli Klinik Pasien Rawat Jalan Menggunakan Metode IAR

Abstract: The hospital is one of the health care facilities with various services helping people who have health probems. Medical record is a file that contains records and data related to patient identity, examination results, treatment history that has been given, other actions and services that have been carried out to patients. This study aimed to describe the completeness of filling the initial polyclinic assessment form. The methode of this study was descriptive analysis. The population of this study were the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…The incompleteness of the initial outpatient assessment documentation in this study was much higher than in previous studies. A previous study by Safitri in 2022 in an outpatient unit showed a completeness rate of 77% (12), and a study by Rajaa at Basra General Hospital identified the incomplete filling of the initial assessment in the medical record, reaching 78% (13).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The incompleteness of the initial outpatient assessment documentation in this study was much higher than in previous studies. A previous study by Safitri in 2022 in an outpatient unit showed a completeness rate of 77% (12), and a study by Rajaa at Basra General Hospital identified the incomplete filling of the initial assessment in the medical record, reaching 78% (13).…”
Section: Discussionmentioning
confidence: 94%
“…The delay in filling out medical records causes when the patient has finished treatment, the medical record has not been filled out completely (33). On the other hand, filling out the initial medical assessment form, which is also part of the service process, will inevitably increase the waiting time, mainly if the doctor is not used to filling it out (12). At Puri Bunda Mother and Child Hospital, the organizational culture that filled out patient's initial medical assessment sheet during accreditation only affected the incompleteness of the form.…”
Section: Individual External Factorsmentioning
confidence: 99%
“…11 The outpatient medical assessment form at least includes the patient's medical history, primary complaint, allergy history, physical examination, diagnosis, and action plan. 12 Based on the Regulation of the Minister of Health of the Republic of Indonesia number 290/Menkes/PER/III/2008, informed consent is an agreement given to a patient or family who has received a complete and detailed explanation regarding the medical action. Informed Consent is closely related to law and ethics.…”
Section: Discussionmentioning
confidence: 99%
“…Arrangements in medical completion will provide legal protection. 12 Law of Republic Indonesia Number 29 /2004 concerning Medical Practice states that "Every medical or dental action that a doctor or dentist will carry out on a patient must receive approval". 14 Chapter 5 of the Indonesian Medical Ethics Code issued by the MKEK IDI doctor (Honorary Council of Medical Ethics of the Indonesian Doctors Association) states that "every act or advice that may weaken psychological or physical endurance must receive the consent of the patient/family and only given for the benefit of the patient and the wellbeing of the patient".…”
Section: Discussionmentioning
confidence: 99%
“…Asesmen awal medis merupakan hal wajib yang dilakukan sebelum pasien di rawat inap atau sebelum tindakan pada rawat jalan di rumah sakit, tidak boleh lebih dari 30 hari, atau riwayat medis telah diperbaharui dan pemeriksaan fisik telah diulangi (Kepmenkes RI, 2022). Masih adanya dokter yang mengatakan bahwa pemberian asesmen awal kepada pasien terkadang lupa dilakukan, dapat dipengaruhi oleh beberapa faktor, diantaranya banyaknya pasien yang datang, kurangnya SDM, dan terlewatnya atau ketidak telitian terhadap pengisian asesmen pasien (Safitri et al, 2022). Maka dari itu, untuk meningkatkan kepatuhan melengkapi asesmen perlu dilakukan evaluasi secara berkala dengan menggunakan checklist untuk menilai tingkat kepatuhan dokter dalam melengkapi asesmen sehingga perlu dilakukan sosialisasi.…”
Section: Metode Penelitianunclassified